The perceptions of CEIT postgraduate students regarding reality concepts: Augmented, virtual, mixed and mirror reality - ARSLAN, AHMET; TAÇGIN, ZEYNEP (SPRINGER, 2017)
The purpose of this study is to determine perception of postgraduate Computer Education and Instructional Technologies (CEIT) students regarding the concepts of Augmented Reality (AR), Virtual Reality (VR), Mixed Reality (MR), Augmented Virtuality (AV) and Mirror Reality; and to offer a table that includes differences and similarities between these concepts. This study also aims to determine the likelihood of CEIT postgraduate students for using the said concepts in education. In this context, the frequently used reality concepts in the CEIT field have been examined from the perspective of the participants and in terms of the following traits: frequency of potential use, perceived usefulness, and perceived effectiveness. The phenomenological method was used in this qualitative study. 10 CEIT graduate students have been the participants of this research; with 4 of these pursuing a PhD and 6 pursuing a Master's Degree. 14 open-ended questions related to AR, VR, MR, AV and Mirror Reality concepts were used throughout semi-structured and face-to-face interviews in order to collect data. Findings show that AR and VR are the most familiar concepts. Participants have several misconceptions about the reality concepts but the least amount of misconception was associated with AR and VR. Most of the participants had no idea about MR and none of them had any idea about Mirror Reality. Findings refer that VR is the most frequently used kind of reality owing to the fact that it can be developed and implemented more easily and there are several AR studies because of its current popularity.
Keywords: Augmented reality; Virtual reality; Mixed reality; Education; CEIT